Genome-Wide Identification, Characterization, and Expression Analysis of Small RNA Biogenesis Purveyors Reveal Their Role in Regulation of Biotic Stress Responses in Three Legume Crops - Garg, Vanika; Agarwal, Gaurav; Pazhamala, Lekha T.; Nayak, Spurthi N.; Kudapa, Himabindu; Khan, Aamir W.; Doddamani, Dadakhalandar; Sharma, Mamta; Kavi Kishor, P. B.; Varshney, Rajeev K. (Frontiers in Plant Science, 2017)
Biotic stress in legume crops is one of the major threats to crop yield and productivity. Being sessile organisms, plants have evolved myriad of mechanisms to combat different stresses imposed to them. One such mechanism, deciphered in the last decade, is small RNA (sRNA) mediated defense in plants. Small RNAs (sRNAs) have emerged as one of the major players in gene expression regulation in plants during developmental stages and under stress conditions. They are known to act both at transcriptional and post-transcriptional levels. Dicer-like (DCL), Argonaute (AGO) and RNA dependent RNA polymerase (RDR) constitute the major components of sRNA biogenesis machinery and are known to play a significant role in combating biotic and abiotic stresses. This study is therefore focused on identification and characterization of sRNA biogenesis proteins in three important legume crops, namely chickpea, pigeonpea and groundnut. Phylogenetic analysis of these proteins between legume species classified them into distinct clades and prompt towards the evolutionary conservation of these genes across the members of Papillionidoids subfamily. Variable expression of sRNA biogenesis genes in response to the biotic stresses among the three legumes indicates the possible existence of specialized regulatory mechanisms in different legumes. This is the first ever study to understand the role of sRNA biogenesis genes in the studied legumes in response to pathogen attacks.